IDENTIFYING TEACHER’S STRATEGIES IN TEACHING WRITING - Irikawati Irikawati (Al-Lisan: Jurnal Bahasa, 2017)
This research discusses about “Identifying Teacher’s Strategies in Teaching Writing”. Then, the problem research are what is the teacher’s strategy in writing and how to identify teacher strategy in teaching writing. The purpose of this study is to determine the teacher’s strategy in teaching writing and identifying the teachers’s strategy in teaching writing. This research is carried out in class XI M.A Nuruttaqwa Limboto. The method used in this research is qualitative method. Respondent in this research is English teacher and student of class XI M.A Nuruttaqwa Limboto. The instrument used to identify the teacher’s strategy in teaching writing is observation and interview. The results of the research indicate the identification of the strategy of English education teacher in teaching writing, there are several strategies used and almost all the steps in the strategy is conducted and implemented well by the English teacher.